Cordial Labeling of Corona Product of Paths and Fourth Order of Lemniscate Graphs (European Journal of Pure and Applied Mathematics, 2025)
A graph $G = (V,E)$ is called cordial if it is possible to label the vertex by the function $f:V→{0,1}$ and label the edges by $%f^*:E→{0,1}$, where $f^*(uv)=(f(u)+f(v)) mod 2$, $u,v\in V$ so that $|v_0-v_1|\le 1$ and $|e_0-e_1|\le 1$.A lemniscate graph is a plane curve with a characteristic shape, consisting of two loops that meet at a central point as shown below. The curve is also known as the lemniscate of Bernoulli. A fourth order of lemniscate graph is a graph of two fourth order of circles that have two vertex in common. In this paper, we give the conditions that the corona product of paths and fourth order of lemniscate graphs be cordial.
Keywords: Cordial labeling; corona product; lemniscate, Social Networking, Network security, Edge Computing